A coesão e a coerência na reescrita de textos elaborados por alunos da Educação de Jovens e Adultos (EJA) - Santos, Maria Aparecida dos (2017)
This dissertation aims to find out how young and adult education students use cohesive elements in rewriting. Based on this general objective, we established as specific objectives: 1) to verify the extent to which the cohesive elements contribute to the coherence in the rewritten texts and 2) to propose rewriting activities for the analysis of the referential and sequential cohesion records that contributed to the textual coherence. The research was applied to 43 students of elementary school, which comprises the complementary stages (in the past, 5th and 6th grades) and the final stages (in the past, 7th and 8th grades) of a municipal school in the south zone of São Paulo city. In order to develop the research, we selected the short story Adivinha, adivinhão, by Luís da Câmara Cascudo, as motivational text to rewriting to verify how referential and sequential cohesion occur, and to distinguish the linguistic strategies used to form the desired logical-semantic relationships, which contribute to the coherence of the texts produced by the students. We provided copies of the text and asked the students to read them and re-read as many times as needed for comprehension and then rewrite the story as closely as the original text. After this activity, we began the analysis. Our theoretical foundations are based on Beaugrande's (1997) text concept and on the concepts of cohesion and coherence defined by Koch (2010), Halliday & Hassan (1976), Antunes (2005), Beaugrande & Dressler (1981) and Koch & Travaglia (2004). The results obtained in the analysis of the rewritten texts indicate that the referential and sequential strategies used by the students are restricted and repetitive, but do not compromise the semantic and pragmatic coherence, so necessary to the interpretability of the text